Anaerobic Oxidation of n-Dodecane by an Addition Reaction in a Sulfate-Reducing Bacterial Enrichment Culture - Kropp, Kevin G. (American Society for Microbiology, 2000)
We identified trace metabolites produced during the anaerobic biodegradation of H(26)- and D(26)-n-dodecane by an enrichment culture that mineralizes these compounds in a sulfate-dependent fashion. The metabolites are dodecylsuccinic acids that, in the case of the perdeuterated substrate, retain all of the deuterium atoms. The deuterium retention and the gas chromatography-mass spectrometry fragmentation patterns of the derivatized metabolites suggest that they are formed by C—H or C—D addition across the double bond of fumarate. As trimethylsilyl esters, two nearly coeluting metabolites of equal abundance with nearly identical mass spectra were detected from each of H(26)- and D(26)-dodecane, but as methyl esters, only a single metabolite peak was detected for each parent substrate. An authentic standard of protonated n-dodecylsuccinic acid that was synthesized and derivatized by the two methods had the same fragmentation patterns as the metabolites of H(26)-dodecane. However, the standard gave only a single peak for each ester type and gas chromatographic retention times different from those of the derivatized metabolites. This suggests that the succinyl moiety in the dodecylsuccinic acid metabolites is attached not at the terminal methyl group of the alkane but at a subterminal position. The detection of two equally abundant trimethylsilyl-esterified metabolites in culture extracts suggests that the analysis is resolving diastereomers which have the succinyl moiety located at the same subterminal carbon in two different absolute configurations. Alternatively, there may be more than one methylene group in the alkane that undergoes the proposed fumarate addition reaction, giving at least two structural isomers in equal amounts.